АВТОМАТИЗИРОВАННАЯ СИСТЕМА СИГНАЛИЗАЦИИ ИЗМЕРЕНИЯ ВЛАГИ - Киямов, Асрор (Innovatsion texnologiyalar, 2022)
This article highlights the application of a system for automated control of grain and air moisture in storage, presents a sensor configuration with an integrated basic microcircuit designed to measure moisture content, and a circuit diagram of the alarm.